Accounting information systems and financial crises: insights into local governments - Dalloul, Mahmoud Hany M.; Ibrahim, Zuraeda Binti; Urus, Sharina Tajul (P.A. Persona e Amministrazione, 2023)
The main purpose of this study is to investigate issues related to accounting information systems and the financial crisis in the Palestinian local authorities. This study follows the qualitative method, as it relied on reports issued by governmental and oversight agencies, scientific articles, previous studies, press statements, and reports published by the Palestinian local authorities and the Palestinian Ministry of Local Government. The most important issues related to the financial crisis and the success of accounting information systems in the Palestinian local authorities were discussed. Thus, the study contributes to enriching the literature related to the Palestinian local authorities' reality. Improving awareness of the reality of accounting information systems and the financial crisis in the Palestinian local authorities. Contribute to establishing an integrated vision of the accounting information systems' role in managing financial crises. The study reached many conclusions, the most prominent of which was that the financial crisis management effectiveness stems mainly from the adoption of successful accounting information systems. The study provided many recommendations and directions for future studies towards a further investigation of the relationship between the success of accounting information systems and the effectiveness of managing financial crises.